EVALUATION OF WATER POLLUTION STATUS IN BAHLUI RIVER (IASI TOWN AREA) DUE TO DOMESTIC AND URBAN WASTEWATER TREATMENT ACTIVITIES - CARMEN ZAHARIA (Journal of Engineering Studies and Research)
This study presents some data about the water pollution status of Bahlui river in Iasi town area (two control sections) mainly due to domestic and urban wastewater treatment activities, considering especially some quality indicators (i.e. nitrogen-based nutrients, total phosphorus and sum organics content) evaluated for 2009-2010. The Bahlui water classification by European standards in Iasi town area corresponds to ‘medium’ (WQI = 53.893 - 64.345). The real water pollution state of Bahlui river (Iasi town area) is estimated by the global pollution index (I*GP), and corresponds to values of 2.80-2.929 (Valea Lupului-Iasi control section), and 3.030-3.196 (Holboca control section, i.e. downstream of Dancu wastewater treatment plant). These values are indicating an aquatic environment modified by domestic and urban wastewater treatment activities, generating discomfort effects, or producing stress against aquatic life forms. These data are recommending application of hydro-ameliorative/remediation actions, and permanent control of Bahlui watercourse quality in all existing control sections.